Biosurfactant As the Next Antimicrobial Agents in Pharmaceutical Applications - Vello, Sumathy; Jamal, Parveen; Alam, Md. Zahangir; Jami, Mohammed Saedi; Mohd. Noor, Wira; Wan Mohd, Fazli (2019)
The number of patients with antimicrobial resistance is growing as a result of new emerging microbes or overuse of antibiotics. A new substitute to the existing antimicrobial agents is important in time to come to control the mortality rate in the global population. Natural substances, like biosurfactants or commonly known as microbial surfactants could be a potential antimicrobial agent to medical personnel’s consideration as some biosurfactants exhibits antimicrobial activity. Hence, this paper will